A novel hotspot of vertebrate endemism and an evolutionary refugium in tropical Australia. Issue 1 (17th November 2016) - Oliver, Paul M.; Laver, Rebecca J.; De Mello Martins, Felipe; Pratt, Renae C.; Hunjan, Sumitha; Moritz, Craig C.
Abstract: Aim: In lineages or regions that are rife with morphologically cryptic taxa, hotspots of local endemism may remain overlooked when genetic data are unavailable. Here we examine the genetic diversity and evolutionary origins of lizard communities occurring in a relatively restricted, isolated and heretofore poorly surveyed region of limestone karst in northern Australia. Location: The Devonian Reef System (DRS), an iconic range of exposed weathered limestone at the margin of the Australian Arid Zone (AAZ) and Monsoonal Tropics (AMT) in north‐west Australia, that is widely recognized for its cultural, geological and palaeontological significance. Methods: In collaboration with local landowners, we sampled four different gecko genera at sites spanning the DRS and adjacent biomes. We then used measures of genetic divergence, neutrality tests, Bayesian dating and hierarchical approximate Bayesian computational (HABC) approaches to identify divergent lineages, test for shared biogeographic history and compare patterns of genetic differentiation in lineages with different ecologies (saxicoline, arboreal and terrestrial). Results: Amongst saxicoline taxa, we identified 11 genetically divergent lineages that appear to be endemic to the DRS. Generalists and arboreal lineages showed no evidence of endemism in the DRS. Estimated divergence dates and patterns of distribution indicate that endemic lineages have persisted since the Plio‐Pleistocene (or even earlier). Taxa in an old endemic Australian Gondwanan radiation showed evidence of longer persistence and isolation than those in radiations with more recent immigrant origins. Main Conclusions: The DRS is a heretofore overlooked hotspot of vertebrate endemism and persistence. Areas with distinctive underlying geology that provide microrefugia (such as karst) in tropical regions across the globe are likely important refugia for biodiversity at both ecological and evolutionary scales. They warrant further focused survey efforts (including genetics‐based assessments of diversity) and ongoing conservation attention.